Authority, Personality and its Effects on Conflict Resolution Behaviour among Students of Istanbul Bilgi University - Gul Arif, Ayesha; Czukor, Gergely (UMT Education Review, 2020)
The aim of this experimental study was to examine how undergraduate students as participants resolve a conflict in response to authority status manipulation of the opponent person (low: a fellow student; high: a university professor), considering the moderating role of participants’ personality traits. 320 Psychology undergraduate students from Istanbul Bilgi University, aged 19-23 participated in an online survey. The participants first completed the Turkish version of the NEO-FFIand then they completed the modified Turkish version of the Thomas-Kilmann Mode Instrument (TKI). It was hypothesised that highly agreeable participants who were faced with a professor in a conflict would show a accommodating resolution style. Whereas extroverted participants who faced a fellow student inwere predicted to displaycompetitiveness in the conflict. A moderated regression analysis was applied. The results showed the opposite effects, students who were in conflict with the professor were more competitive and students who were in conflict with fellow students showed more accommodation. Limitations and future research possibilities are also discussed.